Elasticity and Plasticity of Large Deformations An Introduction - Bertram, Albrecht (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Nonlinear Continuum Mechanics is a rapidly growing field of research. Since the last edition of this book, many important results in this field have been published. This new edition  refers to the most important results.   The part on hyperelastic models and anisotropic yield criteria has been enlarged and an outlook on Material Plasticity has been added.